Analisis Faktor-Faktor Yang Mempengaruhi Audit Report Lag(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek IndonesiaPeriode 2012-2014) - Novy Aristika, Manda (2016)
Audit report lag is the time period in completing the audit work until the date of issuance of audit reports. This study aimed to examine the effect of audit opinion, firm size, firm age, and income to the audit report lag 2012-2014. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2012- 2014. The research sample was determined by purposive sampling method. The sample in this study amounted to 462 companies with outlier data is 63, so that the data obtained a sample of 138 companies. Analysis of data using the multiple linear analysis. The results showed that (1) the audit opinion no significant effect on the audit report lag (2) the size of the company's significant negative effect on the audit report lag (3) the age of the company has no significant effect on audit report lag (4) of income significant negative effect on audit report lag.